Oral Phenotype of Singleton–Merten Syndrome: A Systematic Review Illustrated With a Case Report - Riou, Margot Charlotte; de La Dure-Molla, Muriel; Kerner, Stéphane; Rondeau, Sophie; Legendre, Adrien; Cormier-Daire, Valerie; Fournier, Benjamin P. J. (Frontiers in Genetics, 2022)
Background: Singleton-Merten (SGMRT1) is a rare autosomal dominant disorder, caused by IFIH1 variations, with blood vessels calcifications, teeth anomalies, and bone defects. Aim: We aim to summarize the oral findings in SGMRT1 through a systematic review of the literature, and to describe the phenotype of a 10-year-old patient with a SGMRT1 diagnosis. Results: A total of 20 patients were described in the literature, in 9 articles. Eight IFIH1 mutations were described, in 11 families. Delayed eruption, short roots, and premature loss of permanent teeth were the most described features (100%). Impacted teeth (89%) and carious lesions (67%) were also described. Our patient, a 10-year-old male with a Singleton-Merten syndrome presented numerous carious lesions, severe teeth malposition especially in the anterior arch, and an oral hygiene deficiency with a 100% plaque index. The panoramic X-ray did not show any dental agenesis but revealed very short roots and a decrease in the jaw alveolar bone height. Whole-genome sequencing analysis revealed a heterozygous de novo variant in IFIH1 (NM_022168.4) c.2465G>A (p.Arg822Gln). Conclusions: Confused descriptions of oral features occurred in the literature between congenital findings and “acquired” pathology, especially carious lesions. The dental phenotype of these patients encompasses eruption anomalies (delayed eruption and impacted teeth) and lack of root edification leading to premature loss of permanent teeth and it may contribute to diagnosis. Early diagnosis is essential to prevent teeth loss and to improve quality of life of these patients.